Comparative studies on the morphological, structural and optical properties of NiO thin films grown by vacuum and non-vacuum deposition techniques. (24th December 2021) - Jamal, M S; Chowdhury, M S; Bajgai, Saraswati; Hossain, M; Laref, A; Jha, Pankaj Kumar; Techato, Kuaanan
Abstract: The structural and optical characteristics of Nickel oxide thin films (NiOTF) formed on the soda-lime glass substrate (SLG) under vacuum and non-vacuum conditions are investigated in this work. The difference between RFMS (Radio Frequency Magnetron Sputtering; vacuum) and SP (spray pyrolysis; non-vacuum) was helpful in the development of NiOTF. Deposited films data for this study were characterized by using x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), scanning probe microscopy (SPM), and optical spectrophotometer. Structural studies disclosed that NiOTF developed via RFMS technique was more uniform with large crystals and lower surface roughness in contrast to that of developed via SP technique. Transmittance spectrum divulged that the transmittance of spray pyrolyzed NiO films are ∼10% less than that of ones produced by RFMS. Urbach energy analysis of NiOTF developed by RFMS and SP affirmed the findings of structural studies.